К ВОПРОСУ О ПРЕДЛОЖЕНИЯХ С ЛОКАТИВНЫМ СУБЪЕКТОМ - Darda-Gramatyka, Joanna (Przegląd Rusycystyczny, 2020)
The article is an attempt to present the structures in which the locative element plays the role of the subject, naming the place which a certain feature is attributed to. The lexical material comes from Russian texts belonging to the reproductive register of the speech (the narrative). The analysis was based on the main ideas of Galina Zolotova’s functional grammar concept